International Sourcing and Supply Chain Stability - Levy, David L. (Journal of International Business Studies, 1995)
An international supply chain is conceptualized as a complex, dynamic system in which disruptions interact with long shipping and lead times to generate costs. Findings from a case study and simulation model indicate that demand-related disruptions created substantial and unexpected costs in terms of expedited shipping, high inventories, and lower demand fulfillment. Production-related disruptions declined over time, but demand-related disruptions did not. Implications for management are discussed.